Taxonomy of educational objectives : the classification of educational goals : affective domain - 4 0 16; 1913-, Bloom, Benjamin Samuel,;Masia, Bertram B.; 5 (New York : David McKay Company, Inc., 1964)
Describes the nature of the affective domain and the classification structure prepared for it; gives the classification structure in detail; and describes the evaluation of affective objectives at each level of the structure.
Includes bibliographical references.
Young Adult.
Keywords: 2 -- 0; 6; Aims and objectives. -- Education -- United States -- 20; 20; 2